Bioanalytical Method Development and Validation of Empagliflozin by LC–MS/MS Method and Quantitative Estimation of Drug Concentration in Human Plasma - Dhani, Ramesh (Asian Journal of Pharmaceutics (AJP), 2021)
Objective: The objective of this work is to develop rapid, selective, and sensitive liquid chromatography tandem–mass spectrometry (LC–MS/MS) method for the quantitative estimation of empagliflozin. Sample and standard solutions were prepared using methanol. Methodology: The chromatographic separation was achieved with X Bridge C18 column (75 mm × 4.6 mm, 3.5 μ) using a mobile phase composition of acetonitrile and 10 mM ammonium bicarbonate (70:30 V/V) at a flow rate of 0.8 mL/min with a run time of 2.40 min. The method showed good linearity in the range of 2–1000 ng/mL with correlation coefficient (r) of >0.9998. Results: The % CV of peak area ratio (analyte area/ISTD area) and % CV of retention times for analyte and ISTD were within the acceptance criteria. There was no significant carry over observed during this experiment. All the investigated human plasma lots were found to be free of significant interferences at the retention time of drug and ISTD. The intra- and inter-day precision values for empagliflozin comply with the acceptance criteria. The battery of stability studies, namely, bench-top, freeze-thaw, and long-term stability was performed. All the stability studies showing the % C.V. of area responses for the replicate injections should be within 15%. Conclusion: The developed method was very simple, precise, reliable, sensitive, and robustness. The retention time takes less time consumption and high sensitivity, the method applicable for routine analysis and bioanalysis.